Localization and dynamic change of saponins in Cyclocarya paliurus (Batal.) Iljinskaja - Chen, Xiaoling (PLoS One, 2019)
Cyclocarya paliurus is a unique tree species of that grows in southern China. The tree contains distinctive saponins in the leaf that has hypoglycemic and hypolipidemic effects. It was aimed to detect localization of saponins and suitable time of harvest for medicinal uses. Histochemical, cytochemical localization and UV-spectrophotometry were carried out in C. paliurus plant. We found that in all organs, the saponins were primarily located in the parenchyma cells and the highest saponins accumulation was in the palisade tissue in leaves. Cytochemical localization results indicated that saponins were mainly distributed in the chloroplast, vesicle, and plasmalemma. On average, the total saponins content in leaves (20.57 mg·g(-1)) was two and three times greater than in root (10.19 mg·g(-1)) and shoot (6.20 mg·g(-1)), respectively. Moreover, the saponins content in the leaf and root exhibited fluctuations, which were highest in September. Considering saponins levels and biomass, we conclude that harvesting all leaves in September is an economical and effective strategy for medicinal use in C. paliurus.